The Rise of Muhammadiyah’s Islamic Da’wah in the Contemporary Era: Transformation to Online Trend and Responses to Islamic Moderation - Sholihul Huda; Mohammad Maulana Mas’udi; Nafik Muthohirin (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research explains about the rise of Muhammadiyah’s Islamic da’wah in the contemporary era. In particular, this study aims to describe the transformation of Muhammadiyah’s Islamic da’wah through social media and its response to Islamic moderation in Indonesia. The transformation of online da’wah was absolute, because it was based on the spread of ideology and narration of religious extremism that had been spreading on social media in the last two decades. This research used qualitative approach by strengthening the argumentation building on the research topic through descriptive analysis based on extracting data in the field. Data collection techniques were carried out through in-depth interviews and documentation from various Muhammadiyah online da’wah sites. This research found a new and very important thesis issue, Muhammadiyah experienced a positive trend in strengthening Islamic da’wah strategies on social media. The rise was marked by an increase in the number of new online da’wah portals affiliated with Muhammadiyah. The various da’wah sites seemed innovative and creative in content and professional from the management side, as well as voicing the narrative of Islamic moderation.